Improvement in hot corrosion resistance of dissimilar alloy 825 and AISI 321 CO2-laser weldment by HVOF coating in aggressive salt environment at 900°C - Muthu, S. M.; Arivarasu, M.; Hari Krishna, T.; Ganguly, Supriyo; Phani Prabhakar, K. V.; Mohanty, Saurav (Springer, 2020)
This study investigated the hot corrosion performance of a dissimilar weldment of Ni-based superalloy and stainless steel joined by CO2-laser welding and improved by high-velocity oxy-fuel (HVOF) coating in a Na2SO4-60wt%V2O5 environment at 900°C. A dissimilar butt joint of AISI 321 and alloy 825 was fabricated by CO2-laser welding with low heat input after obtaining the optimum welding parameters by bead-on-plate trials. The metallurgical and mechanical properties of the laser weldment were evaluated. The tensile test results indicated the occurrence of fracture in the base metal AISI 321 side. The HVOF process was employed to coat Ni-20wt%Cr on the weldment. To evaluate the surface morphology of the corrosion products formed on the uncoated and Ni-20wt%Cr-coated weldments, scanning electron microscopy (SEM) analysis was performed. Energy-dispersive spectroscopy (EDS) was used to determine the different elements present on the surface scales. The existence of oxide phases on the weldments was determined by X-ray diffraction (XRD). The cross sections of the weldments were characterized by SEM with EDS line mapping analysis. The results indicated that the Ni-20wt%Cr-coated weldment exhibited superior hot corrosion resistance due to the development of Cr2O3 and NiCr2O4 protective oxide scales.
Keywords: nickel-based superalloy; dissimilar welding; weldment corrosion; high-velocity oxy-fuel coating; corrosion kinetics